Analysis of the Effect of Digital Marketing on Brand Advocacy with Perceived Service Quality and Customer Engagement as Intervening Variables at Fridaytigasports - Puspitasari, Ayu; Permata, Nanda (Journal of Applied Business Administration, 2024)
The purpose of this study is to analyze the effect of Digital Marketing on Brand Advocacy with Perceived Service Quality and Customer Engagement as intervening variables. Data analysis techniques include path analysis quantitative methods using questionnaires distributed to 100 respondents using certain criteria, with a purposive sampling technique. The results of this study are digital marketing has a positive effect on brand advocacy, digital marketing has a positive effect on perceived service quality, digital marketing has a positive effect on customer engagement, perceived service quality has a positive effect on brand advocacy, customer engagement has a positive effect on brand advocacy, Digital Marketing has an influence Brand Advocacy through Perceived Service Quality as an Intervening variable and Digital Marketing influences Brand Advocacy through Customer Engagement as an Intervening Variable